MODIFICATION OF LOCAL ISOLATE LIPASE FOR BIODIESEL SYNTHESIS - Kartika Sari, Diah
Lipase (Triacylglicerol acylhydrolase, E.C. 3.1.1.3) derived from thermophilic bacteria can be used for various industrial purposes. Thermostable lipase derived from thermophilic bacteria such as KHA-P12, isolated from Kawah Hujan Crater, West Java, is predicted to be able to overcome existing problems in industry such as high temperature and longer time process. Lipase is excessively used in fat and oil processing, detergent ingredients, food processing, chemical substance synthesis, pharmacy, paper synthesis, cosmetic products, and biodiesel industry. Biodiesel is one of renewable, environmental-friendly, no-health-effect alternative fuels and can be used as motor vehicle fuel. Lipase can catalyze transesterification reaction in biodiesel synthesis by suitable reagent and with limited water presence. Modification of lipase enzyme to organic soluble lipase is applied to reduce water content that will impede biodiesel synthesis process. This research is aimed to modify thermostable KHA-P12 lipase to organic soluble lipase and to characterize modified lipase in biodiesel synthesis.